Changes in the basis of vitreous body in case of uveitis treated by adalimumab - N.V. Panchenko; T.A. Khramova; A.I. Litvishchenko; G.S. Sarkisian; M.N. Samofalova; E.N. Gonchar; M.V. Friantseva (Ukrainian Society of Ophthalmologists, 2015)
Objective of the research is to study the dynamics of changes in the basis of vitreous body in case of uveitis treated by Adalimumab. Material and methods. 5 year old patient S. with recurrent anterior uveitis on the background of juvenile arthritis was observed. Results. After 4 months of treatment by Adalimumab (20 mg 1 time every 2 weeks combined with methotrexate 10 mg 1 time a week) an exudate has reabsorbed in the prebasal sections of the vitreous body, and after seven months - in the basal ones. During the year no uveitis exacerbations were checked. Conclusions. When uveitis is treated by Adalimumab the exudate is reabsorbed more slowly in basal sections of the vitreous body. Usage of Adalimumab in the treatment of uveitis is effective and in combination with methotrexate helps to prevent relapses.